KAJIAN ESTETIKA FOTOGRAFI POTRET “REKONSTRUKSI BALI TAHUN 1930” KARYA GAMA PHOTOGRAPHY - Arya Putra, I Putu Dudyk (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Portrait photography by GAMA Photography shows a different and unique perspective in it’s concept and presentation. It can not be separated from the idea of an aesthetic visual arts. The achievement of the asthetic value of portrait photography can be seen from it’s form, which is technically designed with unique style and to meet the asthetic criteria that specially conceived, or become the manifestation of idea that becomes the basic of aesthetic creativity. Aesthetic value in portrait photography by GAMA Photography manifested through creation efforts, both ideational and technical by showing theme The Reconstruction of Bali 1930.